Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) 4. ( 1.1/4)2 + [(3/4)2 : (5/4)3] : (3/2)3
= 4.1/16 + [9/16 : 125/64] : 27/8
= \(\frac{1}{4}+\frac{9}{16}:\frac{125}{64}:\frac{27}{8}=\frac{1}{4}+\frac{36}{125}:\frac{27}{8}\)
= \(\frac{1}{4}+\frac{36}{125}.\frac{8}{27}\)
=\(\frac{1}{4}+\frac{32}{375}=\frac{375}{1500}+\frac{128}{1500}=\frac{503}{1500}\)
b] = 2^3 + 3 x 1 - 1 + ( 2^2 x 2 ) x 2^3
= 2^3 + 3 - 1 + 2^3 x 2^3
= 2^3 + 2 + 2^6 = 74
a] = 4 x ( 1/4 )2 + ( 32/42 : 53/43 ) : 27/8
= 4 x 1/16 + ( 32 x 4/53 ) x 8/27
= 1/4 + 36/53 x 8/27 = 1/4 + 4/125 x 8/3 = 503/1500 sấp sỉ 0,335333
b) \(\dfrac{7}{15}-\dfrac{9}{19}\)\(-\dfrac{-8}{15}-\dfrac{10}{19}\)
=\(\left(\dfrac{7}{15}-\dfrac{8}{15}\right)\) \(-\left(\dfrac{9}{19}-\dfrac{10}{19}\right)\)
= \(-\dfrac{1}{15}\) - \(\left(-\dfrac{1}{19}\right)\)
\(=-\dfrac{1}{15}\) + \(\dfrac{1}{19}\)
= \(-\dfrac{4}{285}\)
c) \(1\dfrac{1}{3}\) \(\div\) \(\dfrac{4}{5}\) + 2\(\dfrac{2}{3}\) \(\div\)\(\dfrac{4}{5}\)
= \(\left(1\dfrac{1}{3}+2\dfrac{2}{3}\right)\) \(\div\dfrac{4}{5}\)
= \(\left[\left(1+2\right)+\left(\dfrac{1}{3}+\dfrac{2}{3}\right)\right]\) \(\div\dfrac{4}{5}\)
= ( 3 + 1 ) \(\div\dfrac{4}{5}\)
= 4 \(\div\dfrac{4}{5}\)
= \(\dfrac{4.5}{4}\)
= 5
a) \(\left(0,25\right)^3\cdot32=0,015625\cdot32=0,5\)
b) \(\left(-0,125\right)^3\cdot80^4=\dfrac{-1}{512}\cdot40960000=80000\)
c) \(\dfrac{8^2\cdot4^5}{2^{20}}=\dfrac{2^{3^2}\cdot2^{2^5}}{2^{20}}=\dfrac{2^6\cdot2^{10}}{2^{20}}=\dfrac{2^{16}}{2^{20}}=\dfrac{1}{2^4}=\dfrac{1}{16}\)
d) \(\dfrac{81^{11}\cdot3^{17}}{27^{10}\cdot9^{15}}=\dfrac{3^{4^{11}}\cdot3^{17}}{3^{3^{10}}\cdot3^{2^{15}}}=\dfrac{3^{44}\cdot3^{17}}{3^{30}\cdot3^{30}}=\dfrac{3^{61}}{3^{60}}=3\)
a, ( x-1)3= -27
=> x - 1 = -3
=> x = -2
b, ( 2x - 1)2=25
=> 2x - 1 = 5 hoặc 2x - 1 = -5
=> 2x = 6 hoặc 2x = -4
=> x = 3 hoặc x = -2
c, ( x - 3/4)2= ( 1/2)6
=> (x - 3/4)^2 = 1/64
=> x - 3/4 = 1/8 hoặc x - 3/4 = -1/8
=> x = 7/8 hoặc x = 5/8
d, 2 x + 2 x +2 = 80
=> 2^x + 2^x.4 = 80
=> 2^x(1 + 4) = 80
=> 2^x.5 = 80
=> 2^x = 16
=> x = 4
e, 4x + 4 x + 3 = 4160
=> 4^x(1 + 64) = 4160
=> 4^x.65 = 4160
=> 4^x = 64
=> x = 3
a) \(A=2^{24}=\left(2^3\right)^8=8^8.\)(1)
\(B=3^{16}=\left(3^2\right)^8=9^8\)(2)
Từ (1) và (2) \(\Rightarrow A< B\)
Vậy \(A< B.\)
b) \(B=\left(0,3\right)^{30}=\left(0,3^2\right)^{15}=0,09^{15}\)(1)
\(A=\left(0,1\right)^{15}\)(2)
Từ (1) và (2) \(\Rightarrow A>B\)
Vậy \(A>B.\)
c) \(A=\left(\frac{-1}{4}\right)^8=\left(\frac{1}{4}\right)^8=\left[\left(\frac{1}{2}\right)^2\right]^8=\left(\frac{1}{2}\right)^{16}\)(1)
\(B=\left(\frac{1}{8}\right)^5=\left[\left(\frac{1}{2}\right)^3\right]^5=\left(\frac{1}{2}\right)^{15}\)(2)
Từ (1) và (2) \(\Rightarrow A>B\)
Vậy \(A>B.\)
d) \(A=102^7=102^6.102\)(1)
\(B=9^{13}=9^{12}.9=\left(9^2\right)^6.9=81^6.9\)(2)'
Từ (1) và (2) \(\Rightarrow A>B\)
Vậy \(A>B.\)
e) \(8A=8\frac{8^{18}+1}{8^{19}+1}=\frac{8^{19}+8}{8^{19}+1}=1+\frac{7}{8^{19}+1}\)(1)
\(8B=8\frac{8^{23}+1}{8^{24+1}}=\frac{8^{24}+8}{8^{24}+1}=1+\frac{7}{8^{24}+1}\)(2)
Từ (1) và (2) \(\Rightarrow8A>8B\Rightarrow A>B\)
Vậy \(A>B.\)
f) \(A=\frac{5^5}{5+5^2+5^3+5^4}=\frac{5^4}{1+5+5^2+5^3}=\frac{625}{156}>\frac{468}{156}=3.\)(1)
\(B=\frac{3^5}{3+3^2+3^3+3^4}=\frac{3^4}{1+3+3^2+3^3}=\frac{81}{40}< \frac{120}{40}=3.\)(2)
Từ (1) và (2) \(\Rightarrow A>B\)
Vậy \(A>B.\)
a, ta có A=2^24=64^4
B=3^16=81^4
Vì 64^4<81^4
Vậy 2^24<3^36
b, ta có A=0,1^15
B=0,3^30=0,09^15
Vì 0,1^15< 0,09^15
Vậy 0,1^15<0,3^30
a,(0,125.8)3=13=1
b,(-39:13)4=(-3)4=81